UL a suite for 1 male, 1 female, and orchestra - Kyungsook, Um
This particular work is meant to explore a new world of contemporary music which would be a synthesis of a classical idea and the experimentalistic contemporary process. The expressive subject of the work is "UL" the essence of Korean soul.